Knowledge and Practice in the Malaria Prevention in Community of Kupang City and Kupang District - Lona, Elshaday Yunita; Wanti; Rahmawati, Ety; Sila, Oktovianus; Singga, Siprianus; Sadukh, Johannes Pitreyadi (proceedinginternational, 2023)
Malaria is a public health problem in the world, including in Indonesia and Nusa Tenggara Timor (NTT) Province. Kupang District was including the highest malaria cases in NTT in the last 3 years. Kupang City was including the lowest malaria cases in the last 3 years. This study aims to determine the level of knowledge about malaria and community actions in malaria prevention in Kupang City and Kupang District. This descriptive survey was conducted with variables were knowledge about malaria and practice in malaria prevention. The samples in this study were people in Kupang City and Kupang District, with inclusion criteria: 17 years old or older, able to read and write, domiciled in Kupang City or Kupang District and can fill out the google form link that was distributed. The sample size is 100 people in each selected district or a total of 200 people with accidental sampling technique. The results of the study on the level of public knowledge about malaria in Kupang City and Kupang District were different, namely for the Kupang City it was 79 people in the good category (79%) and for Kupang District it was in the sufficient category, namely 40 people (40%). Community actions in malaria prevention in Kupang City and Kupang District are included in the poor category, namely for Kupang City 56 people (56%) and for Kupang Regency 72 people (72%). It is hoped that the community will further increase actions in malaria prevention. For puskesmas to provide counseling to the community more often.